Pengaruh Lingkungan Kampus Dan Motivasi Keuangan Pada Pengelolaan Uang Saku Mahasiswa Universitas Indraprasta - Rendika Vhalery (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
The aim of this research is to test the impact of college environment and financial motivation toward money allowance management. This research was done in Indraprasta University PGRI (Unindra) Jakarta at October to December 2018. The population in this sample is Unindra Economic major student with total 1229 students. The research samples are 273 students by using sampling technique is simple random sampling. The result shows 1) college environment variable coefficient result toward money allowance management is rejected. Means, there is no influence from college environment toward Unindra’s student money allowance management, 2) financial motivation variable coefficient result toward money allowance management is accepted. Means, there is a significant influence of financial motivation toward Unindra’s student money allowance management, 3) The results of college environment variable and financial motivation variable toward money allowance management is accepted. Means, there is a significant influence on the college environment and financial motivation toward money allowance management.